MAGNETIC-PULSE TREATMENT OF GARDEN STRAWBERRY SEEDS - A. I. Kutyrev; D. O. Khort; R. A. Filippov; Yu. S. Tsench (Сельскохозяйственные машины и технологии)
Currently, there are many techniques, products, technologies, technical means, etc. for targeted impact on seed crops and the environment their development, with the aim of obtaining stable yields. Along with traditional methods to improve productivity there are alternative, such as low-frequency pulsed electromagnetic fields. The authors give classification of methods of strawberry seeds preparation for sowing and present the results of a laboratory experiment on the irradiation of Zenga Zengana variety seeds. The effect of pulsed low frequency magnetic field on seed germination and growth of strawberry seedlings at different conditions of treatment (frequency, duty cycle and exposure and exposure time) was established experimentally. The data obtained in the experiment are statistically processed. Confidence intervals for mathematical expectations for each experiment were determined. Germination energy of the seeds treated by a pulsed magnetic field was changed from 29 to 47 percent, germination was from 34 to 48 percent. The maximum of the increment of germination of irradiated seeds compared to control sample was 14 percent. The best germination corresponds to the 16 Hz frequency of exposure and 360 seconds exposure time when 5 mT induction. A further increase time and frequency of exposure reduced germination energy by 5 percent. The pulsed electromagnetic fields affect positively the linear dimensions of sprouts. The average root length in the experimental variant (16 Hz, 360 seconds) compared to the control was greater by 24 percent; sprouts height increased by 28.2 percent and weight by 33.3 percent. The pulsed low frequency electromagnetic fields could be put to good use to improve sowing qualities of the garden strawberry seeds.